Raton couple celebrates 60th (Raton Range Raton, New Mexico, 1992)
Newspaper Article on the 60th Anniversary of Ross and Hester Faver.
Master list item #: 67
File location is in the Raton File Cabinet
Keywords: Faver, Ross; Faver, Hester; Faye, Sidney; Faye, Wilma; Cochran, Randall; Cochran, Rhonda; Hill, Carl; Hill, Cindy; Hill, Thad; Faver, George; Faver, Jerry; Emax, Kent; Emax, Pat; Zimmerman, Sam; Zimmerman, Mary; Zimmerman, Russel; K-Bobs Resaurant; Biography; Local History; Life and Customs; Marriage; Celebration; Anniversary; Raton, New Mexico; Capulin, New Mexico; Alamosa, Colorado; Del Norte, Colorado; Colby, Kansas; Tucumcari, New Mexico; Castle Rock, Colorado; La Junta, Colorado